Risk Analysis of Modest Housing Projects Scheduling using Monte Carlo Simulation - Mochammad Fikri Nur Djohim; Arief Setiawan Budi Nugroho; Tantri Nastiti Handayani (Civil Engineering Dimension, 2024)
It is crucial to address uncertainties in the construction project scheduling to mitigate delays. Probabilistic simulation offers a viable alternative method. This study examined the relationship between project duration and delay risks, as well as identified the most influential activities for modest housing projects using Monte Carlo Simulation. The simulation analysis, which included 2547 iterations, found that, on average, it took 87.39 days to complete a 54-type modest house project, with the shortest and longest durations being 44 and 149 days, respectively. The sensitivity analysis revealed that finishing works, such as painting, doors/windows installation, and cleaning, had the highest uncertainty and significantly affected the project duration. Additionally, the severity analysis showed that wall work was the most impactful activity contributing to delays. Based on these analyses, both finishing works and wall work were identified as the most critical activities significantly influencing the project's completion duration.